Reproducción de los peces en embalses en cascada en un río andino tropical (Colombia) (2018)
ABSTRACT: Variations in rainfall and river level have been identified as the most crucial factors in freshwater fish reproduction in the tropics. Dams and reservoirs change the seasonality of these factors, so fish must develop new tactics to continue reproducing themselves. Our objective was to define the period and sites of reproduction of fish in the middle Porce River drainage, which has been modified by the construction of two reservoirs in cascade (reservoirs Porce II and Porce III). Sampling was carried out from September 2011 to December 2016, during contrasting climatic periods (drought and rains) at 31 sites distributed as follows: in the reservoirs of Porce II and Porce III, in the river channel (above Porce II reservoir, between the reservoirs and below Porce III dam) and tributary streams to two reservoirs. The fish were captured with gillnet, seines and electro-fishing gear. The Vazzoler scale (1996) was used to determine the gonadal development, the gonadosomatic relationship was also estimated and these data were used to make the analysis of the reproductive seasonality of the fi sh assemblage, which was defined according to the reproductive intensity (RI) and the percentage of mature individuals of the species. The results showed that in the reservoirs the fi sh reproduce intensely independent of the climatic period, whereas in streams and river a similar tendency is observed, but with an increase of reproduction associated with the dry season. However, the species Brycon henni particularly had a higher percentage of mature individuals during rainy periods in the Porce III reservoirs and in its tributary streams.